Smart molecular butterfly: an ultra-sensitive and range-tunable ratiometric thermometer based on dihydrophenazines. Issue 2 (21st November 2019) - Song, Wenxuan; Ye, Wenqiang; Shi, Lijiang; Huang, Jinhai; Zhang, Zhiyun; Mei, Ju; Su, Jianhua; Tian, He
Abstract : Ultra-sensitive and range-tunable ratiometric thermometers were developed by controlling the excited-state configuration transformation of a dihydrophenazine derivative via aggregation and disaggregation. Abstract : Ratiometric thermometry with ultra-high sensitivity and tunable response range has been realized in a single molecular system by making full use of the excited-state configuration transformation of a dihydrophenazine derivative (dibenzo[ a, c]phenazine-9, 14-diylbis(4, 1-phenylene))bis(methylene) bis(icosanoate), (DPC). By facilely manipulating the disaggregation and aggregation of DPC, the excited-state configuration transformation could be controlled, thus affording a ratiometric response to temperature change. By altering the composition of the ethanol/glycerol mixtures, the temperature response region could be finely tuned and the overall linear range is as broad as 49.1 °C (−11.4–37.7 °C). Surprisingly, apart from the relative sensitivity as high as around 2000% per °C, which is the highest among all reported luminescent thermometers, and the good repeatability (stability), the present thermometry scheme can even allow the temperature to be read out accurately from the fluorescence (FL) colour since the precise functional relationship between the CIE coordinates of the fluorescence colour and temperature was established. This is unprecedented for luminescent thermometers, meaning that there is no need for the luminescence-based thermometer to rely on a spectrometer. In this way, the application scope of luminescence-based thermometers could be significantly enlarged. The strategy proposed here solves the conflict between high sensitivity and wide temperature response range masterfully.